Improve Listening Comprehension In English - Daulay, Anysah; Sipahutar, Mirna Rismala Rosi Raihan; Siregar, Usman Rialdi; Daulay, Tuah Akbar; Lubis, Yani (Yayasan Daarul Huda Kruengmane, 2024)
This research aims to find out how to improve listening comprehension in English in Uinsu students of the 2nd semester education management study program to improve listening comprehension in English. This research explores the extent to which students improve listening comprehension through films with and without subtitles, music, radio, and heard podcasts in English and what was their attitude towards this teaching tool. In order to be able to hear well, understand the meaning of each word, sentence, when talking to the other person in English. This research used qualitative methods, namely interviews and observations carried out directly in the MPI 2 class, interviews with several students and forming study groups to carry out teaching in improving listening comprehension in English, and taking several documentation as evidence that the research had been carried out. The results of this research are that MP2 class students' listening comprehension in English has increased after learning in study groups. Ways to improve students' listening comprehension in English are by watching films, listening to the radio, listening to music, and listening to podcasts in English. In this way students are able to improve their listening comprehension in English